A impossível flor de Narciso: o fascínio da imagem em Um sopro de vida, de Clarice Lispector - Oliveira, Ângelo Bruno Lucas de (2019)
This research aims to delineate the conception of literature outlined in Um sopro de vida, by Clarice Lispector. From the ideas of Maurice Blanchot and other important 20th century thinkers, this work points to trace the characteristics of the literature that makes this commentary and to identify how they manifested in the corpus of the research. Thus, starting from the image of Narcissus, we describe the general aspects of this literature, whose brand is the fragmentary writing, the emptying of the plot, the rejection of traditional elements of literary texts and questioning to traditional critics. These characteristics are confronted with the object of the research. Then, they are described according its manifestation there. This manifestation corroborates, in many aspects, the thought of the evoked scholars. In the last part of the work, we analyze the critic commentaries that Um sopro de vida makes about itself and the literature in general. We identify that the book conceive the writing as impossible and paradoxical activity, marked by incompleteness and the attempt to apprehend an interdicted origin. The theoretical foundation about the literature that we approach Narcissus come from Maurice Blanchot (1980, 1997, 2005, 2010a, 2010b, 2011), Barthes (1999, 2004, 2007a, 2007b, 2010), Didi-Huberman (1998, 2011) and Perrone-Moisés (1973, 2005, 2007, 2009, 2016). The scholars that help us with a more accurate comprehension about Lispector text are Sá (1979, 2004), Sant‟Anna (2013), Helena (1991, 2010), Nunes (1995, 2009), Faria (2016) and Homem (2012).